Analisis Pemeliharaan Mesin Blowmould dengan Metode RCM di PT. CCAI - Noor Ahmadi; Nur Yulianti Hidayah (Jurnal Optimasi Sistem Industri, 2017)
PT. Coca-Cola Amatil Indonesia is a company that produces carbonated beverages. Most of the production activity uses automatic machines. The problem faced is the damage that often occurs suddenly on the blowmould machine so that corrective maintenance must be done. The purpose of this research is to know the cause of the damage and to propose the action plan to minimize downtime. The method used is Reliability Centered Maintenance to determine the selection of action and time interval of replacement for critical components on the blowmould machine. From the FMEA analysis, it is known that the critical components of each blowmould machine subsystem are bearing roller feed, mandrel, seal gasket, and fitting. The results of LTA analysis are the category of failure (outage problem and economic problem) and the selection of action for the critical component (time directed). From the calculation of Total Minimum Downtime, known that the replacement schedule for critical component are 23 days for bearing roller feed, 9 days for mandrel, 8 days for seal gasket, and 8 days for fitting, that is resulting in decreased downtime of 1.56% with a value of 99.63% availability.